Strengthening Integrity Through Anti-Corruption Education in Elementary Schools - Lisma Meilia Wijayanti (Edujavare Publishing, 2025)
This study analyzes the role of anti-corruption education in strengthening integrity among elementary school students. The research aims to examine how anti-corruption values such as honesty, responsibility, discipline, and fairness are integrated into school learning and how they influence students’ character development. A qualitative descriptive method with a case study approach is used, with data collected through observation, interviews, and documentation. The findings indicate that anti-corruption education is effectively implemented through value integration in classroom learning, teacher role modeling, and school habituation practices. Students demonstrate improved integrity when exposed to consistent and contextual value-based education. However, challenges remain in ensuring consistency between school-based learning and the broader social environment. The study concludes that continuous and collaborative efforts between schools, families, and society are essential for strengthening students’ integrity through anti-corruption education.